2013
DOI: 10.1155/2013/714564
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Therapy of Gastroesophageal Reflux in Preterm Infants

Abstract: Although gastroesophageal reflux (GER) is a very common phenomenon among preterm infants, its therapeutic management is still an issue of debate among neonatologists. A step-wise approach should be advisable, firstly promoting nonpharmacological interventions and limiting drugs to selected infants unresponsive to the conservative measures or who are suffering from severe GER with clinical complications. Despite of this, a concerning pharmacological overtreatment has been increasingly reported. Most of the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 124 publications
(172 reference statements)
0
14
0
2
Order By: Relevance
“…In the 2004 survey, 30% of units used pH monitoring on a regular basis (3). The current survey revealed that still only a minority of units (34%) were using pH monitoring, perhaps reflecting the poor correlation between symptoms and the results of investigations (7) and/or the problems with interpreting the results. Reflex events are diagnosed if there is a reduction in the oesophageal pH below four.…”
Section: Discussionmentioning
confidence: 72%
“…In the 2004 survey, 30% of units used pH monitoring on a regular basis (3). The current survey revealed that still only a minority of units (34%) were using pH monitoring, perhaps reflecting the poor correlation between symptoms and the results of investigations (7) and/or the problems with interpreting the results. Reflex events are diagnosed if there is a reduction in the oesophageal pH below four.…”
Section: Discussionmentioning
confidence: 72%
“…Une excellente revue parue en 2013 attire l'attention sur les méfaits de certaines thé-rapeutiques en insistant sur la prudence des décisions [13].…”
Section: Chez Le Prématuréunclassified
“…Antacids such as ranitidine and omeprazole are gastric acid secretion inhibitors and are commonly prescribed to preterm babies across neonatal intensive care units (NICUs) for management of reflux symptoms and GORD despite little evidence for efficacy and safety of their use in this age group [1, 3, 6, 7]. Prescription is in an off-labelled manner in preterm infants due to their perceived safety and possible benefits [3, 811].…”
Section: Introductionmentioning
confidence: 99%
“…Prescription is in an off-labelled manner in preterm infants due to their perceived safety and possible benefits [3, 811]. Gastric juice acidity, however, provides a major non-immune defence barrier against infections in neonates [12]; hence the use of gastric inhibitors has been shown in various studies to assist onset of infections in preterm infants and children leading to morbidity and mortality [1, 1215].…”
Section: Introductionmentioning
confidence: 99%